(untitled) (UNED Research Journal, 2026)
Introduction: Self-care is essential for health promotion and disease prevention through intentional behaviors aimed at maintaining holistic well-being. Objective: To describe self-care behaviors across age groups among staff using a Costa Rican public higher education institution. Methods: We did a cross-sectional study with the Self-Care Behavior Scale (ECA). A total of 737 individuals participated (67% of the target population). Results: Emotional and social self-care obtained the highest scores (>8), followed by physical self-care (>7), while spiritual self-care showed the lowest scores. Significant age-group differences were identified across all dimensions. Individuals over 50 years reported more frequent emotional, social, and spiritual self-care practices, and demonstrated more controlled consumption of fast food compared with younger groups. Conclusion: Age plays a relevant role in self-care behaviors. Staff over 50 years exhibited higher engagement in emotional, social, and spiritual self-care, highlighting the need to strengthen strategies targeted at younger workers.